2022
DOI: 10.1007/s11033-022-07148-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a static magnetic field and baicalin or baicalein interactions on amelanotic melanoma cell cultures (C32)

Abstract: Background Baicalin and baicalein have antioxidant, anti-inflammatory, hepatoprotective and anti-cancer properties. However, it is not known how a static magnetic field will modify these properties. Therefore, the aim of our study was to evaluate the simultaneous exposure of melanoma cells to flavones and the static magnetic fields that are generated by permanent magnets on the gene expression and the activity of the antioxidant enzymes that are associated with the antioxidant defense system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Moreover, in their studies, Sabo et al [34] confirmed that an SMF with an induction of up to 1 T may have an anticancer effect on leukemic cells (HL-60). On the other hand, in our previous research, we found that a static magnetic field (0.7 T) eliminated the anticancer effects of baicalin and baicalein in melanoma cells [35].…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, in their studies, Sabo et al [34] confirmed that an SMF with an induction of up to 1 T may have an anticancer effect on leukemic cells (HL-60). On the other hand, in our previous research, we found that a static magnetic field (0.7 T) eliminated the anticancer effects of baicalin and baicalein in melanoma cells [35].…”
Section: Discussioncontrasting
confidence: 53%
“…Our previous studies show that an SMF with an induction of 0.7 T does not cause disturbances in redox homeostasis in normal cells and cancer cells [ 16 ]. However, simultaneous exposure of cancer cells to an SMF and antioxidants commonly found in food and dietary supplements abolishes the anticancer effect of these substances [ 17 , 18 ]. Moreover, in a study by Wang et al [ 14 ], it was found that a static magnetic field can inhibit the development of osteosarcoma, which is the effect of free radical processes dependent on iron ions.…”
Section: Discussionmentioning
confidence: 99%